2016
DOI: 10.1177/0271678x16631149
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of cerebral blood flow using phase contrast magnetic resonance imaging and duplex ultrasonography

Abstract: Phase contrast magnetic resonance imaging (PC-MRI) and color-coded duplex ultrasonography (CDUS) are commonly used for measuring cerebral blood flow in the internal carotid (ICA) and vertebral arteries. However, agreement between the two methods has been controversial. Recent development of high spatial and temporal resolution blood vessel wall edge-detection and wall-tracking methods with CDUS increased the accuracy and reliability of blood vessel diameter, hence cerebral blood flow measurement. The aim of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 21 publications
1
50
0
Order By: Relevance
“…In such cases, an alternative method may be phase-contrast MRI combined with the time-of-flight angiography. In our previous study, we found that colorcoded duplex ultrasonography and phase-contrast MRI have the similar estimations of volumetric CBF measured from the internal and vertebral arteries (Khan et al 2017).…”
Section: Methodological Considerationsmentioning
confidence: 66%
See 1 more Smart Citation
“…In such cases, an alternative method may be phase-contrast MRI combined with the time-of-flight angiography. In our previous study, we found that colorcoded duplex ultrasonography and phase-contrast MRI have the similar estimations of volumetric CBF measured from the internal and vertebral arteries (Khan et al 2017).…”
Section: Methodological Considerationsmentioning
confidence: 66%
“…In our previous study, we found that color‐coded duplex ultrasonography and phase‐contrast MRI have the similar estimations of volumetric CBF measured from the internal and vertebral arteries (Khan et al . ).…”
Section: Methodological Considerationsmentioning
confidence: 97%
“…The main limitation of our study is the lack of confirmation with MR imaging that has a higher specificity and sensitivity for VA diameter measurement . However, B‐mode ultrasound was performed by the same expert professional sonographers in order to visualize the VA according to their best knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…However, B‐mode ultrasound was performed by the same expert professional sonographers in order to visualize the VA according to their best knowledge. Moreover, evidence supports the use of Color Doppler ultrasound for cerebral blood flow velocity measurements in the VA against MRI, which is not the case for VA diameter measurement . On the other hand, flow velocities are also influenced by systemic (eg, blood pressure, heart rate, heart failure, hematocrit values, etc) and local (eg, coiling, kinking, and external constriction) factors beyond the degree of stenosis, which can change the vertebral flow velocities as well.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the mean of the PLS-defined regional CBF values was not associated with memory performance. Our choice of the upper velocity cut-off that was comparable to previous work (Khan et al, 2017), but could have introduced some bias in the phase contrast CBF quantification. Another possibility is the potential of ceiling effects in the CBF or RAVLT measures, as this group included cognitively intact 50-year-old adults.…”
Section: Sensitivity Analysesmentioning
confidence: 99%